In vitro gas production and digestibility of oat and triticale forage mixtures ensiled with fibrolytic enzymes and inoculants (Agro Productividad, 2024)
Objective: To assess the effects of adding fibrolytic enzymes (FE) or lactic acid bacteria (LAB) inoculants to 40 d silages with oat and triticale (O:T) mixtures on the ratio and composition of neutral detergent fiber (NDF) and its subsequent in vitro gas production (GP) and in vitro dry matter digestibility (IVDMD) at 24 h.Design/Methodology/Approach: Silages elaborated with two O:T ratios (60:40 and 80:20) treated with low (LD), medium (MD), and high (HD) doses of FE (0.75, 1, and 1.25 g/kg forage in wet basis (WB), respectively), and LAB (0.188, 0.25, and 0.31 g/kg WB, respectively). In both cases (FE and LAB), the control had a value of 0. Subsequently, pH, NDF, acid detergent fiber (ADF), acid detergent lignin (ADL), hemicellulose (HEM), cellulose (CEL), dry matter (DM), crude protein (CP), GP parameters, and IVDMD were assessed. GP parameters included maximum velocity (Vmax), fractional rate (S), and lag. Experiments were planned in complete randomized designs (CRD), including factorial and split-plot arrangements. Variance analysis (ANOVA) models included fixed (doses, additives, and FR) and random (place/moment of sampling) effects.Results: LAB improved the IVDMD at 24 h of 60:40 and 80:20 O:T silages. FE did not reduce the NDF of 60:40 silages, but LD and MD increased the HEM and CP, and reduced the ADF, ADL, and CEL; these results are correlated (r) with the improvement of pH pattern, GP, and IVDMD.Study Limitations/Implications: The differences in the NDF of FR mixtures could affect the effectiveness of FE and LAB.Findings/Conclusions: Although FE and LAB did not reduce the NDF, they changed the ratios of ADF, ADL, HEM, CEL, and CP of silages, potentially improving the GP and IVDMD.